Deformation Imaging by Strain in Chronic Heart Failure Over Sacubitril‐Valsartan: A Multicenter Echocardiographic Registry. (29th November 2022) - Mandoli, Giulia Elena; Pastore, Maria Concetta; Giannoni, Alberto; Benfari, Giovanni; Dini, Frank Lloyd; Rosa, Gianmarco; Pugliese, Nicola Riccardo; Taddei, Claudia; Correale, Michele; Brunetti, Natale Daniele; Mazzeo, Pietro; Carluccio, Erberto; et al.
Abstract: Aims: Sacubitril/valsartan has changed the treatment of heart failure with reduced ejection fraction (HFrEF), due to the positive effects on morbidity and mortality, partly mediated by left ventricular (LV) reverse remodelling (LVRR). The aim of this multicenter study was to identify echocardiographic predictors of LVRR after sacubitril/valsartan administration. Methods and results: Patients with HFrEF requiring therapy with sacubitril/valsartan from 13 Italian centres were included. Echocardiographic parameters including LV global longitudinal strain (GLS) and global peak atrial longitudinal strain by speckle tracking echocardiography were measured to find the predictors of LVRR [= LV end‐systolic volume reduction ≥10% and ejection fraction (LVEF) improvement ≥10% at follow‐up] at 6 month follow‐up as the primary endpoint. Changes in symptoms [New York Heart Association (NYHA) class] and neurohormonal activations [N‐terminal pro‐brain natriuretic peptide (NT‐proBNP)] were also evaluated as secondary endpoints; 341 patients (excluding patients with poor acoustic windows and missing data) were analysed (mean age: 65 ± 10 years; 18% female, median LVEF 30% [inter‐quartile range: 25−34]). At 6 month follow‐up, 82 (24%) patients showed early complete response (LVRR and LVEF ≥ 35%), 55 (16%) early incomplete response (LVRR and LVEF < 35%), and 204 (60%) no response (no LVRR and LVEF < 35%). Non‐ischaemic aetiology, a lower left atrial volume index, and a higher GLS were all independent predictors of LVRR at multivariable logistic analysis (all P < 0.01). A baseline GLS < −9.3% was significantly associated with early response (area under the curve 0.75, P < 0.0001). Left atrial strain was the best predictor of positive changes in NYHA class and NT‐proBNP (all P < 0.05). Conclusions: Speckle tracking echocardiography parameters at baseline could be useful to predict LVRR and clinical response to sacubitril–valsartan and could be used as a guide for treatment in patients with HFrEF.